Influence of medium‐chain fatty acids and short‐chain organic acids on jejunal morphology and intra‐epithelial immune cells in weaned piglets. Issue 3 (25th February 2016) - Ferrara, F.; Tedin, L.; Pieper, R.; Meyer, W.; Zentek, J.
Summary: Medium‐chain fatty acids (MCFA) and short‐chain organic acids (SOA) are often used as feed additives in piglet diets. There are limited studies in pigs describing the impact of MCFA or SOA on gut morphology and the local immune system. The aim of this study was to investigate whether the supplementation of SOA (0.41% fumaric acid and 0.32% lactic acid), or the combination of SOA with MCFA (0.15% caprylic and capric acid) would have effects on gut morphology and intestinal immune cells in weaned piglets. A total number of 72 weaned piglets were randomly allocated into three experimental groups. Tissue samples of six animals per group were used to investigate the potential impact of the feed additives on villus length and crypt depth of the jejunum and to quantify intra‐epithelial lymphocytes (IEL). CD3‐positive IEL were determined via immunohistochemistry (IHC) and flow cytometry (FC), whereas CD2−, CD5−, CD8β−, CD16− and γδ TCR‐positive IEL were only analysed by FC. The supplementation of MCFA and SOA did not significantly affect morphometric data. The FC data indicated that SOA significantly increased the quantity of CD2 − CD8 − γδ T cells in the jejunum epithelium. Both IHC and FC analyses of pig jejunum confirmed that the majority of IEL expressed the surface marker CD3 and could be classified as cytotoxic T lymphocytes. In conclusion, the data indicated that SOA increased the proportion of CD2 − CD8 − γδ T cells in the jejunal epithelium. Thus, SOA might enable a beneficial effect on the local immunity by increasing the constitutive number of potential effector cells to defeat infectious diseases.